Origin of near-surface hydrocarbon gases bound in northern Barents Sea sediments. (April 2019) - Weniger, Philipp; Blumenberg, Martin; Berglar, Kai; Ehrhardt, Axel; Klitzke, Peter; Krüger, Martin; Lutz, Rüdiger
Abstract: In the southern part of the Norwegian Barents Sea extensive hydrocarbon exploration and drilling has led to several oil and gas discoveries, yet little is known on the petroleum systems and potential hydrocarbon reservoirs in the northern Norwegian Barents Sea. If hydrocarbons generated by thermogenic processes deep in the subsurface migrate to the surface, traces of these hydrocarbons can remain in the near-surface sediments and provide indirect information on potential petroleum systems. Near-surface hydrocarbon prospecting is a method frequently used in hydrocarbon exploration of frontier areas, where no direct geochemical information from drilling is available. To improve knowledge of subsurface structures and the evolution of potential petroleum systems in the northern Barents Sea, seismic data and near-surface sediment samples were collected. Analysis of bound hydrocarbon gases extracted from these sediments revealed concentrations significantly above background in areas along the Hornsund-Knøllega Fault Complex as well as near margins of the Olga Basin. Generally, the compositional and stable carbon isotope signatures of bound gases indicate thermogenic origins from source rocks of oil window maturity for near-surface gases with anomalous high concentrations, whereas for sediments with low concentration of bound gases, mixture of thermogenic and microbial gas is indicated. Amount and composition of bound gas extracted from source rock samples from Spitsbergen indicate that contribution of transported material may have influenced the bound gas in near-surface marine sediment of the Barents Sea in areas where presence of mature organic matter is indicated. In the Knølegga Fault Complex near the western Barents Sea margin high concentrations of thermogenic gas in near-surface sediments are associated with fault-bound basins and most likely originate from the Paleocene-Eocene Torsk Formation. In the Olga Basin higher bound gas concentrations occur near the southern border of the basin corresponding to sub-cropping Late Jurassic – Early Cretaceous shales, whereas elevated concentrations in the northern Olga Basin are associated with reactivated faults, reaching close to the surface. Sediments above the center of the basin show significantly lower bound gas concentrations. These observations indicate that the Jurassic shales act as a regional seal for hydrocarbons and that reactivated faults at the basin margin represent pathways for migration to the surface. 1D basin and petroleum systems modeling for the Olga Basin indicates that Early to Middle Triassic sediments reached oil window maturity and represent the most likely source for thermogenic near-surface gas in that area. Highlights: Bound gas anomalies in northern Barents Sea at western margin and Olga Basin. Gas isotope signature indicates origin from oil window mature source rocks. Potential source rocks evaluated from 2D seismic data and 1D petroleum systems model.